Sistemas integrados de produç\~ao: Potenciais opç\~oes para o Brasil - Júnia Cristina P. R. da Conceiç\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work aimed to analyze the potential of integrated systems technology in Brazil. Initially, an identification of works that identify, in this technology, the possibility of production with environmental respect, in view of the internal and external demand of this type of production with environmental sustainability. The paper presents a description of the regional distribution of integrated systems in Brazil. It also presents the regional distribution of agricultural production and livestock production based on the locational quotient index, locational Gini index and production redistribution index. The results found indicate that Brazil has a diversified agricultural production and, in some cases, with a regional concentration. Livestock production is also diversified, and also presents a regional concentration. It was also verified by the studies carried out, mainly by the Brazilian Agricultural Research Corporation (Embrapa - Empresa Brasileira de Pesquisa Agropecuária), that there is a diversity of integration options and that some have the potential for development in Brazil, mainly using sheep as a livestock component. Brazil also has to face some challenges, which include, mainly, the strengthening of the financing system to guarantee the capacity of implementation of this technology by the producers, the development of researches for the viability of the diverse modalities of integration and technical assistance to guarantee that the best technologies can be used.
Keywords: Q01; Q10; 330; integration systems; regional concentration indices; integration options